(Mis)understandings and uses of 'culture' in bioethics deliberations over parental refusal of treatment: Children with cancer. (June 2018) - Gray, Ben; Brunger, Fern
We developed this study to examine the issue of parental refusal of treatment, looking at the issue through a cultural competence lens. Recent cases in Canada where courts have declined applications by clinicians for court orders to overrule parental refusal of treatment highlight the dispute in this area. This study analyses the 16 cases of a larger group of 24 cases that were selected by a literature review where cultural or religious beliefs or ethnic identity was described as important reasons behind the refusal. The most significant finding was that nearly all of the cases cited unacceptable side effects as the main reason for declining treatment. We then analysed the detail of the cases and concluded that in the first instance a skilled clinical approach to develop an agreed management plan is by far the best approach. In the event that agreement cannot be reached we recommend engaging a mediator to help the clinician and parents/child to find an agreeable way forward. We argue that the option of seeking a court order was of significant detriment to many of the children in our cases and that this option should be used sparingly. There is a need for empirical research on the outcome of cases where a court order is sought.